Flash! : - Schilling, Govert (Cambridge University Press, 2002)
Gamma ray bursts are the biggest explosions since the Big Bang. Until their accidental discovery by secret military satellites, no-one knew of their existence. Now astronomers all over the world are searching for these mysterious bursts of gamma rays, which are thought to be signs of the creation of black holes billions of light years away. Based on interviews with leading scientists, Flash! describes the exciting and fast moving field of gamma ray burst research.